Penggunaan Sistem Pendukung Keputusan Seleksi Atlet Silat Sekotawaringin Timur Menggunakan Metode Simple Additive Weighting - Norman, Norman; Rosida, Rosida; Putri, Shinta; Nurahman, Nurahman (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
This study discusses a case that wants to be completed using the SAW (Simple Additive Weighting) method. Some people are often confused and confused, how to solve the problem of a case using methods that have been applied. Basically all the problems and all the cases that we want to solve or want to find the decision-making system are enough with some methods that we want to do. Here the method used is the SAW method, the SAW method is very easy to understand and to be used in various cases. One of the examples discussed here is the case of searching for a selection of silat athletes from East Sekotawaringin East from 1 to 100 people will be tested and judged from the determined alternatives, until in the end searching and finding which champion 1 of 100 people who get the best rank.